A New Routing Algorithm for Hierarchical Wireless Sensor Networks - Hussain , Rana (University of Thi-Qar Journal of Science, 2015)
Wireless sensor networks (WSNs) have become an interesting area to researchers in recent years due to the lowcost of sensor nodes, wide application areas and with low or no cost of maintenance after deployment in a target area. In some sensor system applications, the nodes are hard to reach and it is impossible to replace their batteries. So the nodes must operate without battery replacement for a long time. Such conditions make the system power consumption a very crucial parameter. Thus, Clustering is an energy efficient way that divides sensor nodes into many clusters, each of which has a cluster head. In this paper a new cluster-based routing algorithm for hierarchical WSNs has been proposed to select an alternative node to get replaced in place of node which loses its energy such that it extends the lifetime of entire network and avoids data loss. The simulation results show that, for large scale WSNs, our proposed algorithm performs better than the typical existing routing algorithms in terms of network lifetime.